Non-destructive detection of CMAS damage on thermal barrier coatings using AC impedance technique - Yuki HAYASHI (The Japan Society of Mechanical Engineers, 2016)
Thermal barrier coatings (TBCs) on high temperature components in gas turbine engines are in some cases damaged by calcium-magnesium-alumino-silicates (CMAS) resulting from the ingestion of siliceous minerals at high temperatures exceeding 1200°C. An attempt to develop a non-destructive detection technique of CMAS damage on TBCs was carried out through an AC impedance technique in this work. The CMAS-affected TBC specimens were prepared by simulating the CMAS damage in laboratory, employing a synthetic CMAS product. The change in electric capacitance was measured by using an LCR meter. It was found that the capacitance of the ceramic top coat showed higher value at CMAS infiltrated areas, compared with that at the non-infiltrated ones. While the capacitance increased with increasing infiltration depth, the change in capacitance of the TBC specimen decreased when the CMAS enhanced the delamination damage of TBC top coat. Some discussion was made on the changes in capacitance using a simple condenser model, so that the present electric technique is applied to the CMAS damage detection and evaluation.